Cold abscess of thigh following inadvertent vaccination in an infant (Indian Journal of Child Health, 2016)
Localized abscess in the same site of bacillus Calmette-Guerin (BCG) vaccine is a known complication. However, the occurrence of such abscess at other sites is uncommon. We, hereby, report a case of 4-month-old female child who developed a swelling at left thigh following intramuscular injection at 6 weeks vaccination. Aspiration cytology of abscess showed granulomatous inflammation and positivity for acid-fast bacilli. The exact etiology for this presentation is unknown; however, wrongful inoculation of the BCG vaccine in place of DPwT vaccine at 6 weeks could be suspected. Mycobacterium should be considered in any unexplained soft tissue abscessin areas of the world where tuberculosis is prevalent.